Spatial Variability of Soil Factors Affecting Irrigated Lowland Rice Yield - Warris, Mohd Nasir (2002)
Spatial variability of soil chemical and physical properties, and its influence on leaf nutrient content, and yield components were studied in a 0.95 ha rice field in Kuala Selangor. A total of 120 soil samples at 15 cm depth and 120 samples of rice plant were taken at harvesting stage based on grid point sampling of 10m x 10m. The studies revealed that coefficients of variation for soil physical properties were in the order of bulk density > soil moisture > clay content. Soil chemical properties showed coefficients of variation in the order of K > Mg >total-N > CN ratio> P> Ca > total-S > total-C and Cu > Zn > Na > Mn > pH. The coefficients of variation for leaf nutrient content were found to be in the sequence of Cu > Zn> P > K> Mg > N > Na > Mn > Ca. The range for soil physical properties was found to be in the order of bulk density (134 m) > soil moisture (100 m) > clay content (17 m), while the range for soil chemical properties was in the sequence of Mg (21 8 m) > total-C (161m) > pH (134 m) 2: total-S (134 m) 2:P (134 m) > Ca (120 m) > total-N (54 m) > CN ratio (46 m) > Na (41 m) > Mn (35 m) > Cu (20 m) > Zn (15 m).